Issues on the Use of Grammar in Students' Final Report Writings in English Department of Sriwijaya State Polytechnic - Ridhwan, Moehamad; Risnawati; Sri Gustiani; Herman (Politeknik Negeri Sriwijaya, 2023)
ABSTRACT: This study was conducted to analyze the students’ final report writings in the English Department of State Polytechnic of Sriwijaya. It was trying to discover if the students were still making grammatical mistakes in their final writing project or if such a thing was already non-existent. When the mistakes had been found, the English grammatical points were referred to to classify the kinds of mistakes that had occurred. Percentage was also made to indicate the most frequently found grammatical errors down to the least. From here it would seem that the students’ writings were only full of grammatical mistakes, but that was because this article focused on the mistakes. The correct structures being occupied remained unattended, as it was not the theme of this article. Again, the results of this study could not be interpreted as the students having bad writing skills. It was just that their good structural points were not to be brought up for discussions as it was not the topic in this particular research. In addition, the writing papers being chosen were the ones that had been examined in the students’ report presentation seminar and been kept in the library of the English department which anyone could easily access. After the research was done, the findings were rather beyond expectation. The students made wrong use of even the simplest structures like past tense, to be, and plural forms of nouns. However, it was presumably and more likely due to them being careless and not because of their ignorance on the matter. Keywords: grammatical errors, writing skills, ignorance